Effect of Plant Growth Promoting Rhizobacteria (PGPR) and Arbuscular Mycorrhizal Fungi (AMF) on Salt Stress Tolerance of Casuarina obesa (Miq.) - Diagne, Nathalie; Ndour, Maty; Djighaly, Pape Ibrahima; Ngom, Daouda; Ngom, Marie Claver Ndébane; Ndong, Ganna; Svistoonoff, Sergio; Cherif-Silini, Hafsa (Frontiers in Sustainable Food Systems, 2020)
Salinity is one of the main abiotic stresses limiting plant growth and development. However, the use of salt-tolerant plants combined with beneficial soil microorganisms could improve the effectiveness of biological methods for saline soil recovery. The aim of this study is to identify the Casuarina obesa/ Arbuscular Mycorrhizal fungal (AMF)/ Plant Growth Promoting Rhizobacteria (PGPR) association that could be used in salt-land rehabilitation programs. Thus, the plants were grown under greenhouse on sandy soil, inoculated either with PGPR (Pantoea agglomerans and Bacillus sp.), or with AMF (Rhizophagus fasciculatus and Rhizophagus aggregatum) or co inoculated with PGPR and AMF and watered with a saline solution (0, 150 and 300 mM). After four months of cultivation, the plants were harvested and the results obtained showed that inoculation improves the survival rate, height and biomass of the plants compared to the control plants. The results also showed that inoculation increases the total amount of chlorophyll and the accumulation of plant proline at all levels of salt concentration. However, P. agglomerans and Bacillus sp. strains alone or in combination with R. fasciculatus increased plant growth. This study showed that these strains of PGPR, whether or not associated with AMF, could be used as a biological tool to improve C. obesa performance under saline stress conditions.